2011
DOI: 10.1590/s1517-86922011000500006
|View full text |Cite
|
Sign up to set email alerts
|

Ativação muscular do quadril e do joelho em duas aterrissagens realizadas por atletas do sexo masculino

Abstract: Objective: To compare the myoelectric activity before and after ground contact between single-leg (SL) and double-leg (DL) landings in male athletes. Participants: Fifteen male volleyball athletes without signs and symptoms of lesions in the lower extremities, with a minimum of three years experience in the sport (13 ± 1 years, 1.70 ± 0.12 m, 60 ± 12 kg). Measurements: Participants performed two vertical jumps, landing unilaterally and bilaterally. The myoelectric activity of the rectus femoris (RF), biceps fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Our results indicate that a greater lateral symmetry in the THTD test is related to a lower AJ (r = −0.58, p = 0.01), which is not easily explained. In the basic technique of the volleyball attack jump, the take-off is done with both feet at the same time [15], suggesting that there should be a better performance in the AJ the more symmetrical the player is, which is the opposite of what our results have shown.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Our results indicate that a greater lateral symmetry in the THTD test is related to a lower AJ (r = −0.58, p = 0.01), which is not easily explained. In the basic technique of the volleyball attack jump, the take-off is done with both feet at the same time [15], suggesting that there should be a better performance in the AJ the more symmetrical the player is, which is the opposite of what our results have shown.…”
Section: Discussioncontrasting
confidence: 94%
“…Specifically, the jump is done with the drive of the two legs together, but opposite to the forward attack arm, to favor the hip-trunk rotation and to perform a greater force hitting the ball [14]. On the other hand, there is an eccentric landing action within each jump, with an involvement in the creation of these lateral decompensations, where 40% of the landing actions are performed on one leg [15]. All of this seems to indicate that this sport could generate lateral asymmetries that could affect the jumping or ball hitting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has observed an acute pivoting knee adaptation where the fatigue induced by soccer playing appears to be the most relevant source of pivot shift alteration. As our results showed significant differences detected in the static pivot shift test but not in the dynamic pivoting landing task, the more knee muscle activation required during the landing of the pivoting task would help maintain the knee stability (Leporace et al, 2011), even if there was a decreased passive stability (laxity), such as the pivot shift maneuver suggests have occurred in our study.…”
Section: Discussionmentioning
confidence: 48%
“…As predicted, this finding was because of the dynamic pivoting landing task, which has shown more sensitivity to completing insufficient ACL (Pan et al, 2020). Instead, the dynamic testing increases the muscle activation to control the landing (Leporace et al, 2011). Therefore, the sensitivity to detect the axis movement alteration using the dynamic test following a competitive soccer match could be less than that with the pivot testing to find rotatory knee alterations in non-complete insufficient ACL.…”
Section: Discussionmentioning
confidence: 90%
“…Although lower knee extensor RFD to reach 60 and 90% of MIT was correlated with the reduced sagittal movements at the knee and hip, no relationships of hip muscle capacity with sagittal kinematics were identified. This suggests the quadriceps may be more important to control landing movements in comparison with the hip musculature (24). Improving ability to land with less stiffness (i.e., more flexion) (44) may require exercise therapy to improve quadriceps RFD, not just movement retraining, which is typically the focus of knee injury prevention programs (2).…”
Section: Discussionmentioning
confidence: 99%